Pengembangan Bahan Ajar Bahasa Arab Berbasis Aplikasi Android - Evi Muzaiyidah Bukhori; Ahmad Sulton (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
The covid 19 pandemic has had an impact on the education sector, especially in learning Arabic. To increase the effectiveness and efficiency of distance learning, Arabic teaching materials are needed that are easily accessible anywhere and anytime. Arabic teaching materials can be designed in an attractive and innovative way through the Flip PDF Professional application which will later produce Arabic teaching materials in the form of interactive E-books, which contain Arabic materials and are equipped with animations, pictures and audio so that they can attract interest in learning Arabic. Specifically, this article aims to describe the design of developing Arabic language teaching materials based on professional flip pdf applications and determine its validity and feasibility for Kiai Haji Achmad Siddiq Jember State Islamic University (UIN) students. This research uses the type of R&D with the ADDIE development model. The instruments used in this study were validation questionnaire for three experts (media, material and design), and initial interview guidelines. As for testing the data validation results using a Likert scale level of achievement. The results of the research are based on the results of expert trials, product development of Arabic teaching materials gets a score of 91.3% (very good/interesting category) from media experts, validation of material experts gets a score of 97.3% (very good/interesting category), validation design experts get a score of 94.6% with (very good/attractive category). The suggestions and input from the validator are used as guidelines in improving Arabic language teaching materials based on Android applications Abstrak Pandemi covid 19 berdampak pada bidang pendidikan khususnya dalam pembelajaran bahasa Arab, untuk meningkatkan efektivitas dan efisiensi pembelajaran jarak jauh dibutuhkan bahan ajar bahasa Arab yang mudah diakses dimanapun dan kapanpun. Bahan ajar bahasa Arab dapat didesain secara menarik dan inovatif melalui aplikasi Flip PDF Professional yang nantinya akan menghasilkan bahan ajar bahasa Arab berupa E-book interaktif, yang berisi materi-materi bahasa Arab serta dilengkapi animasi, gambar, dan audio sehingga dapat menarik minat dalam mempelajari bahasa Arab. Secara spesifik, Artikel ini bertujuan untuk mendeskripsikan desain pengembangan bahan ajar bahasa Arab berbasis aplikasi flip pdf profesional dan mengetahui validitas dan kelayakannya bagi Mahasiswa UIN Kiai Haji Achmad Siddiq Jember. Penelitian ini menggunakan jenis R&D dengan model pengembangan ADDIE. Instrumen yang digunakan dalam penelitian ini adalah angket validasi untuk tiga ahli (media, materi dan desan) dan pedoman wawancara awal. Adapun pengujian data hasil validasi menggunakan skala likert tingkat pencapaian. Hasil penelitian berdasarkan hasil uji coba ahli, pengembangan produk bahan ajar bahasa Arab mendapat skor sebesar 91,3% (kategori sangat baik/menarik) dari ahli media, validasi ahli materi mendapatkan skor 97,3% (kategori sangat baik/menarik), validasi ahli desain mendapatkan skor 94,6% dengan (kategori sangat baik/menarik). Adapun saran dan masukan dari validator dijadikan pedoman dalam perbaikan produk bahan ajar bahasa Arab berbasis aplikasi Android